Preparation and Characterization of a Collagen-Liposome-Chondroitin Sulfate Matrix with Potential Application for Inflammatory Disorders Treatment. (15th May 2014) - Craciunescu, Oana; Gaspar, Alexandra; Trif, Mihaela; Moisei, Magdalena; Oancea, Anca; Moldovan, Lucia; Zarnescu, Otilia
Abstract : Smart drug delivery systems with controllable properties play an important role in targeted therapy and tissue regeneration. The aim of our study was the preparation and in vitro evaluation of a collagen (Col) matrix embedding a liposomal formulation of chondroitin sulfate (L-CS) for the treatment of inflammatory disorders. Structural studies using Oil Red O specific staining for lipids and scanning electron microscopy showed an alveolar network of nanosized Col fibrils decorated with deposits of L-CS at both periphery and inner of the matrix. The porosity and density of Col-L-CS matrix were similar to those of Col matrix, while its mean pore size and biodegradability had significantly higher and lower values (P < 0.05 ), respectively. In vitro cytotoxicity assays showed that the matrix system induced high cell viability and stimulated cell metabolism in L929 fibroblast cell culture. Light and electron micrographs of the cell-matrix construct showed that cells clustered into the porous structure at 72 h of cultivation. In vitro diffusion test indicated that the quantity of released CS was significantly lower (P < 0.05 ) after embedment of L-CS within Col matrix. All these results indicated that the biocompatible and biodegradable Col-L-CS matrix might be a promising delivery system for local treatment of inflamed site.